Effects of Post Harvest Handling on Corn Quality (Zea mays L) in Kabangka District, Muna Regency - mulianingsih, sitti; Rianda, La; Herdhiansyah, Dhian (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This research aims: 1). To find out how to post-harvest management in Kabangka District. 2). To determine the effect of post-harvest handling on the quality of maize in the Kabangka District. This study uses multiple regression analysis with the help of SPSS 20 for windows. This study uses purposive with the consideration that the District of Kabangka is one of the Districts that have good prospects of corn. The number of respondents in this study was 45 people. The results of this study are 1). Workforce experience has a significant effect on water content, and levels of impurities have a very significant effect while broken grains, other colors, and broken grains have no significant effect on labor experience. Long drying does not significantly affect the moisture content and other color grains. whereas for broken grains, broken grains and impurities have no significant effect. The amount of base used has a very significant effect on water content, broken grains, and broken grains, while other color grains and impurities do not affect the amount of base used. 2). Corn quality with SNI reference can be seen in 2004 the maximum SNI water content is 14,15,17, the maximum broken item is 2,4,6,8, other color items are maximum 1,3,7 10, the maximum broken grain is 1,2,3 and maximum impurities content of 1, 2. From the five samples, two samples meet SNI standards, corn water content meets SNI standards